2012
DOI: 10.1002/mrm.24501
|View full text |Cite
|
Sign up to set email alerts
|

Contrast and stability of the axon diameter index from microstructure imaging with diffusion MRI

Abstract: The ActiveAx technique fits the minimal model of white matter diffusion to diffusion MRI data acquired using optimized protocols that provide orientationally invariant indices of axon diameter and density. We investigated how limitations of the available maximal gradient strength (Gmax) on a scanner influence the sensitivity to a range of axon diameters. Multishell high-angular-diffusion-imaging (HARDI) protocols for Gmax of 60, 140, 200, and 300 mT/m were optimized for the pulsed-gradient-spin-echo (PGSE) seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
218
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(234 citation statements)
references
References 24 publications
15
218
0
1
Order By: Relevance
“…Speed and length of axons generate conduction delays, which together with parameters of postsynaptic integration (Budd and Kisvarday 2012) provide the time frame for brain dynamics. So far, the diameter of axons has been obtained by histological investigations, although this now seems about to change (Barazany et al, 2009;Alexander et al, 2010;Dyrby et al, 2012). Instead, the length of axons can, in principle, be obtained from diffusion MRI tract tracing (DTT), although this approach requires validation by histological methods.…”
Section: Introductionmentioning
confidence: 99%
“…Speed and length of axons generate conduction delays, which together with parameters of postsynaptic integration (Budd and Kisvarday 2012) provide the time frame for brain dynamics. So far, the diameter of axons has been obtained by histological investigations, although this now seems about to change (Barazany et al, 2009;Alexander et al, 2010;Dyrby et al, 2012). Instead, the length of axons can, in principle, be obtained from diffusion MRI tract tracing (DTT), although this approach requires validation by histological methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Alexander et al developed ActiveAx [11], which allows the estimation of orientationally-invariant indices of axon diameter and density in scan time tolerable by live human subjects. ActiveAx uses a Minimal Model of White Matter Diffusion (MMWMD) with four compartments to describe the measured dMRI signal [11,12]: besides the restricted and hindered compartments previously considered by [13], the MMWMD accounts also for stationary water trapped within small structures such as glial cells as well as free water characterised by isotropic diffusion. ActiveAx was recently extended to allow axon diameter mapping also in regions with crossing fibres [14] and thus, overcome the main limitation of the majority of microstructure imaging methods which are restricted to regions with one single fibre orientation.…”
Section: Introductionmentioning
confidence: 99%
“…ActiveAx was recently extended to allow axon diameter mapping also in regions with crossing fibres [14] and thus, overcome the main limitation of the majority of microstructure imaging methods which are restricted to regions with one single fibre orientation. All the techniques mentioned so far have demonstrated the practical possibility to estimate microstructural information from dMRI data and the estimated microstructural indices have been shown to agree very well with known anatomical patterns observed with histology [11,15,12]. However, the non-linear routines usually employed to fit these models are computationally very intensive and cause practical problems for their application in clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The contrast in the in vivo results may therefore reflect the detection of relatively large axon radii in certain parts of the corpus callosum—although our fits from substrates containing gamma distributions of radii suggest that while qualitatively meaningful, our axon radius index values are likely to be overestimates. Nevertheless, while Alexander et al 4 and Dyrby et al 8 have suggested that only very weak sensitivity to axon radius index is available at clinical gradient strengths, we have shown that using suitable priors can ameliorate the situation.…”
Section: Discussionmentioning
confidence: 56%